Quality analysis of village fund management on the success of development program in Letneo Village, Insana Barat District, Timor Tengah Utara Regency - Pangastuti, Margareta (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Letneo Village is one of the villages located in Insana Barat District, North Central Timor Regency which is geographically directly adjacent to the Democratic State of Timor Leste. As a village that has just been divided in the last 5 years, it has also received a large and varied amount of village funds from the central government. Village governments often encounter difficulties in managing village funds due to the lack of quality human resources. Recognizing this, the aim of this research is to determine the effect, either partially or simultaneously, between the variables of planning, implementation and monitoring of village funds on the success of Letneo village development. The analytical tool used is by using multiple linear regression analysis by taking samples from the entire village apparatus of Letneo, totaling 35 people. The results showed that either partially or simultaneously the variables of planning, implementation and supervision had a real and significant influence on the success of the development of Letneo Village, Insana Barat District, North Central Timor Regency.